Problems and Needs in Patients With Incurable Esophageal and Pancreaticobiliary Cancer. (January 2015) - Uitdehaag, Madeleen J.; Verschuur, Els M. L.; van Eijck, Casper H. J.; van der Gaast, Ate; van der Rijt, Carin C. D.; de Man, Rob A.; Steyerberg, Ewout W.; Kuipers, Ernst J.; Siersema, Peter D.
<x xml:space="preserve">Abstract</x> Patients with incurable esophageal cancer (EC) or pancreaticobiliary cancer (PBC) often have multiple symptoms and their quality of life is poor. We investigated which problems these patients experience and how often care is expected for these problems to provide optimal professional care. Fifty-seven patients with incurable EC (N = 24) or PBC (N = 33) from our outpatient clinic completed the validated "Problems and Needs for Palliative Care" (PNPC) questionnaire and two disease-specific quality of life questionnaires, European Organization for Research and Treatment in Cancer (EORTC). Although patients in general had several problems, physical, emotional, and loss of autonomy (LOA) problems were most common. For these physical and emotional problems, patients also expected professional care, although to a lesser extent for LOA problems. Inadequate care was received for fatigue, fear, frustration, and uncertainty. We conclude that an individualized approach based on problems related to physical, emotional, and LOA issues and anticipated problems with healthcare providers has priority in the follow-up policy of patients with incurable upper gastrointestinal cancer. Caregivers should be alert to discuss needs for fatigue, feelings of fear, frustration, and uncertainty.